Polygynous family structure and child undernutrition in Nigeria - Amare, Mulubrhan; Arndt, Channing; Mahrt, Kristi; Mavrotas, George (International Food Policy Research Institute, 2020)
There is a growing interest in the research literature in exploring how child nutrition is affected by sociocultural practices, such as polygyny. However, evaluation of the effect of polygyny on child nutrition has been hindered by the complexity of the relationship. This paper investigates the effect of polygyny on anthropometric outcomes while recognizing that unobservable household characteristics may simultaneously influence both the decision to form a polygynous union and the ability of the household to adequately nourish children. Polygyny can affect children’s nutrition through increased family size, early marriage, and the level of household investment in child health. In this paper, we apply an instrumental variable approach based on the occurrence of same sex siblings in a woman’s first two births to generate exogenous variation in polygyny. Using data from the 2008 and 2013 Nigeria Demographic and Health Surveys, we find a detrimental effect of polygyny on child undernutrition, with a greater effect in poorer households and those resident in more urban locations.